Respiratory protection: scanning electron microscopy study of mask filters (Research, Society and Development, 2022)
Objective: to analyze, through scanning electron microscopy, the morphology of filters in N95/PFF2 masks with and without activated carbon. Method: analytical study, carried out at the Laboratory of Electronic Microscopy and Microanalysis of a university located in northern Paraná. To compose the samples, masks from known brands that were available at the university hospital at the time of the study were acquired: PFF2 mask with activated charcoal, PFF2/equivalent N95 mask. In the laboratory, the samples were prepared and evaluated in the Scanning Electron Microscopy device. Results: All masks had four layers of synthetic polypropylene fibers. The difference presented is in the size of the fibers, the fibers in the filtering layer have from 1 to 5mm and the fibers in the structural layers measure from 15 to 20mm. It was possible to observe openings in the meshes of the filtering layer, with variations between the masks. Conclusion: it is possible to analyze the morphology of the filters of the N95/PFF2 masks, through the analysis of size, distribution and conformation of the fibers, the results indicate that workers who use a high-efficiency mask type N95/PFF2, with activated carbon, during daily exposure to surgical smoke, it decreases the inhalation of particulate materials that are harmful to health in the long term.